Walking the right path: the story of bioresorbable stents - Ellis, Stephen (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
The evaluation of benefit and risk of devices in a given type of patient, cardiac or otherwise, is made more complex in that the results may well depend on the technique applied and accompanying pharmacologic therapies used.